2022-RA-925-ESGO Development of adjuvant treatment decision support tool for endometrial cancer patients by pooled analysis of data from 2000 women included in the PORTEC-1–3 trials and a prospective cohort study. (20th October 2022) - Vermij, Lisa; Putter, Hein; Jobsen, Jan; Powell, Melanie; de Boer, Stephanie; Leary, Alexandra; Bessette, Paul; Mileshkin, Linda; Lutgens, Ludy; Jürgenliemk-Schulz, Ina; Slot, Annerie; van der Steen-Banasik, Elzbieta; et al.
Abstract : Introduction/Background: In 2021, the ESGO-ESTRO-ESP endometrial cancer (EC) guideline was updated and the molecular classification was added to the clinicopathological prognostic factors to classify women with EC in risk groups. The risk stratification is based on consensus of a multitude of studies investigating a variety of EC subgroups. To date, no single study has evaluated all prognostic factors across the complete spectrum of EC. Therefore, we are developing an evidence-based prognostic and therapeutic framework for stage I-III EC that will facilitate risk stratification and support decisions on adjuvant treatment. Methodology: Data from the PORTEC-1/-2/-3 randomised trials (n=714/427/660) and a prospective clinical cohort from Medisch Spectrum Twente (n=270) were pooled for analysis. Competing-risk models for vaginal-, pelvic-, distant-, and overall recurrence and EC-specific survival and a multivariable Cox proportional hazards model for overall survival are being developed. Candidate risk factors are: age, stage, histotype, grade, lymph-vascular space invasion (LVSI), myometrial invasion, molecular classification, L1CAM, CTNNB1, ER status and adjuvant treatment. With these models, absolute risks can be estimated for women with any combination of risk factors by type of adjuvant therapy. Results: In total, 2071 women with EC with a median follow-up of 10.0 years (interquartile range 6.9–12.4 years) are available for analyses. An overview of patient and tumour characteristics is presented in table 1 . The preliminary results of a first version of a prediction model on overall recurrence confirm the prognostic relevance of the established clinicopathological risk factors and the EC molecular class ( table 2 ). Conclusion: The worlds' largest collection of molecularly classified EC with long-term follow-up data was pooled for the development of a prognostic and therapeutic framework. In the next months, we will develop and validate models for other clinical outcomes in order to create a framework that can improve evidence-based risk stratification and support decisions on adjuvant therapy.